Perceptions of university students and teachers on the usefulness and potential of the inclusive metaverse - Segura Berges, Manuel (2026)
Introduction: In recent years, the metaverse has become one of the most prominent technological innovations in the academic field, offering an immersive virtual world with the potential to provide an inclusive response in the teaching-learning process. Objective: To investigate and explore the perceptions of university students and lecturers from the Bachelor’s Degree in Primary Education Teaching regarding the use of the metaverse as an inclusion tool. Method: A qualitative methodology with an interpretative and phenomenological–hermeneutic design was used, involving 109 students and 23 teachers from three universities in Spain. A non-probabilistic purposive sampling was applied, and data were collected through semi-structured interviews and focus groups. Results: Both students and teachers perceived the inclusive potential of the metaverse. However, differences were evident regarding educational functionality and contextual factors. Discussion: The results of this study reflect the digital divide between students and teachers, as well as the need to include training programmes for future teachers.